Improving the Development of Delinquents with a Sports Extracurricular Approach at the Kupang Children's Correctional Institution - Al Ihzan Tajuddin; Salmon Runesi; Ronald Dwi Ardian Fufu; Michael Johannes Hadiwijaya Louk; Jurdan Martin Siahaan; I Nyoman Wahyu Esa Wijaya; Fera Ratna Dewi Siagian (Indonesian Journal of Sport Management, 2023)
Physical education in public schools and children's correctional institutions, especially in extracurricular sports activities, functions as an activity to fill children's free time and is expected to reduce child delinquency. The problems in this study are included in the type of correlational quantitative research, namely research that aims to see the relationship between two or more symptoms that can be measured in high and low relationships using data in the form of numbers. This research uses a descriptive method with quantitative analysis. While the data collection technique for research uses a structured questionnaire based on the research variables. From the results of the study, it can be concluded that there is a positive relationship between extracurricular sports activities and the success of fostering naughty children at the Kupang Children's Penitentiary. this can be seen from the value of r o obtained which is greater than the value of the r table. So, in the future, teachers and staff fostering children should further increase the effectiveness of extracurricular sports activities in fostering naughty children at the Kupang Penitentiary.